The Study of Household Food Security Levels in Palangka Raya City - Wardie, Jhon; Masliani, Masliani; Sintha, Tri Yuliana Eka (Journal of Socioeconomics and Development, 2019)
This study aims to examine the level of household security in Palangka Raya City. This study was carried out in the area of Palangka Raya City which covers five subdistricts. Those include Menteng, Pahandut, Kereng Bangkirai, Tumbang Tahai, and Petuk Bukit. In each sub-districts (kelurahan), 10 household respondents were determined as samples, so the total samples were 50 household respondents. The research data collected were from primary and secondary data. The results of the study revealed that the level of household food security in Palangka Raya City was categorized as food resistance. This category was obtained by using the portion of total food expenditure which did not exceed 60 percent (52.43%, categorized as low), and was sufficient energy consumption exceeding 80 percent of the national recommendation (97.22%, categorized as sufficient). . JEL Classification: D19, Q18, R20